THE IMPORTANCE OF VOCATIONALLY-APPLIED PHYSICAL TRAINING OF YOUNG PEOPLE FOR THE FORMATION OF PERSONNEL RESERVE POWER STRUCTURES OF THE STATE (Fiep Bulletin - online, 2014)
In modern society is essential physical education of youth. The level of physical development of young people largely determines the success of their careers. The purpose of this study was to investigate the influence of physical training for young people to form a reserve of personnel for law enforcement agencies of the state. In the course of this research following methods were used: a theoretical analysis and synthesis of the scientific literature and documentaries, a content analysis of documentary material, sociological and pedagogical methods, methods of studying the dynamics of change of emotional state and physical activity, as well as physical health and performance incidence of respondents, methods of mathematical statistics. More than 86.4% of the young people selected for service in the uniformed services of Ukraine (Ministry of Defense, Ministry of Interior, Ministry of Emergency Situations) in childhood and youth were actively engaged in physical training and participated in sport competitions. Their preliminary physical fitness, particularly the development of such qualities as strength, endurance, speed and agility, enhanced the successful passing of the training programs in the power structures of the state. Given that the majority of young people enrolled in the reserve personnel of the state security forces, in childhood and youth systematically engaged in physical training, and indicators of their strength, endurance, speed and agility characteristics meet the requirements of professional competence, the importance of the state system of physical education of young people is difficult overestimated. Persons who have attained the best results in sports, in most cases more successfully mastered the curriculum of training. This proves the need to adapt the physical training of the population to the professional requirements of the reserve personnel of law enforcement agencies, the use of special programs of professional and applied physical training of youth.
Keywords: young people’s health protection; professionally-applied physical training; the state law enforcement bodies; the level of physical development; the theory; methodology of physical education